2017
DOI: 10.1002/slct.201701752
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Organic Frameworks‐Derived Porous In2O3 Hollow Nanorod for High‐Performance Ethanol Gas Sensor

Abstract: Designing hollow micro/nano structures for gas sensing materials is highly desirable for boosting gas sensing properties and still remains challenging, especially through a simple and economic way. Herein, porous In2O3 hollow nanorod (In2O3‐HNR), which was successfully fabricated by thermal decomposition of an In–MOF (CPP‐3) precursor, was applied as gas sensing materials. The pristine CPP‐3 and obtained In2O3‐HNR were systematically characterized by various techniques, such as XRD, SEM, TEM, TGA‐DTA, XPS, Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…MOFs, a group of organic‐inorganic hybrid materials, are widely used in multiple research fields like gas storage and separation, [19] fuel cells, [20] gas sensor, [21] supercapacitors [22] and photocatalysis [23] because of their unique porous and highly crystalized microstructure [24] . In photocatalysis, materials derived from MOF precursors have large surface area for better light harvesting ability and more active sites [15a,23a] .…”
Section: Introductionmentioning
confidence: 99%
“…MOFs, a group of organic‐inorganic hybrid materials, are widely used in multiple research fields like gas storage and separation, [19] fuel cells, [20] gas sensor, [21] supercapacitors [22] and photocatalysis [23] because of their unique porous and highly crystalized microstructure [24] . In photocatalysis, materials derived from MOF precursors have large surface area for better light harvesting ability and more active sites [15a,23a] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the improvement of people's life, it is significant to monitor toxic and harmful gases timely and effectively. In recent years, metal oxide semiconductors such as ZnO,, SnO 2 ,, In 2 O 3 ,, WO 3 ,, NiO, Co 3 O 4 , etc. have been widely used for gas monitoring because of their high response, simple synthesis and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Hollow one-dimensional (1D) nanomaterials possess a high surface-to-volume ratio and large surface area to facilitate gas adsorption and diffusion, leading to significant enhancement in gas sensing performance. , As is well known, the template is an effective way to obtain a 1D nanomaterials. Recently, metal–organic frameworks (MOFs) have been used as versatile precursors or sacrificial templates to prepare state-of-the-art functional nanomaterials with well-defined structures (hollow and core–shell nanostructures) for different applications by taking after their inherent advantages of porosity, large surface area, and flexible functionality adjustment. , Aside from its direct applications, ongoing studies including this one indicated that MIL-68 (In) can be converted into In 2 O 3 , , In 2 S 3 , and their hybrids for applications such as gas sensors and photocatalysts. Furthermore, studies have revealed their promising capabilities and thus show enhanced performance of gas sensors by the addition of a foreign component in the form of dopants or surface decoration.…”
Section: Introductionmentioning
confidence: 99%